Dynamic recovery actions in multi-objective liner shipping service with buffer times. Issue 2 (22nd June 2022) - Wen, Xin; Ge, Ying-En; Yin, Yuqi; Zhong, Meisu
Abstract : This paper investigates the dynamic recovery policies for liner shipping services with the consideration of buffer time allocation and uncertainties. The aim of this study was to allocate the buffer time at the tactical level and then determine optimal options of actions, including speed optimisation strategy, port skipping and acceleration rate choice, for recovering from disruptions due to various uncertainties or random adverse events, which cause vessel delays. To achieve this, an attempt was made to obtain the optimal balance among economic, environmental and service reliability objectives. A novel mathematical formulation is introduced to solve the robust vessel scheduling problem with short- and long-term decisions. Furthermore, two heuristics were tested to solve the proposed model. Experiments on a container liner shipping service showed the validity of the model and a set of managerial insights were gained from them.